A comparative analysis of phytochemical constituents and bioactivity of two wild medicinal herbs of the Amaranthaceae family - Das, Jinti Moni; Nath, Namita; Sarma, Anindita; Tayung, Kumananda (Plant Science Today, 2024)
Alternanthera sessilis and Alternanthera paronychioides are 2 common herbaceous plants in the North Eastern region of India. The 2 species are known traditionally for edibility and medicinal use. The objectives are to qualitatively screen phytochemicals and test for antioxidant activity and antimicrobial activity between the 2 species– Alternanthera sessilis and Alternanthera paronychioides. The samples for analysis were collected from aerial leaves and air-dried for phytochemical screening and biological activity tests. Antioxidant assays used are DPPH (2,2-diphenyl-1-1picrylhydrazyl), H2O2, and FRAP (ferric reducing antioxidant power) assay. For antimicrobial tests, 2 different strains of microbes were used to test the bioactivity of the plants. Phytochemical screening showed the presence of several antioxidant potential groups of phytochemicals like phenols, flavonoids, etc. Phytochemical constituents of Alternanthera sessilis showed more antioxidant potential than Alternanthera paronychioides in DPPH and H2O2 assays but Alternanthera paronychioides showed more potential than Alternanthera sessilis in FRAP assay. The phytochemicals also showed positive tests for antimicrobial activity against 2 bacterial strains, i.e., Escherichia coli (MTCC 443) and Staphylococcus aureus (MTCC 737). This study reveals the presence of phytonutrients which suggest the antioxidant and antibacterial activities exhibited by the 2 species of the family. Further exploration of phytochemicals in different aspects could lead to better-performing drugs for various ailments.